2019
DOI: 10.3748/wjg.v25.i18.2251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prophylactic clip placement following endoscopic mucosal resection of large colorectal lesions on delayed polypectomy bleeding: A meta-analysis

Abstract: BACKGROUND The role of prophylactic clipping for the prevention of delayed polypectomy bleeding (DPB) remains unclear and conclusions from prior meta-analyses are limited due to the inclusion of variety of resection techniques and polyp sizes. AIM To conduct a meta-analysis on the effect of clipping on DPB following endoscopic mucosal resection (EMR) of colorectal lesions ≥ 20 mm. METHODS We performed a search of PubMed and the Cochrane libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
4
25
0
1
Order By: Relevance
“…found that prophylactic clipping did not reduce the occurrence of delayed bleeding after colorectal endoscopic resection regardless of the lesion size, which the vast majority of the cases enrolled in the analysis are lesions < 20 mm (2847 out of 3059; 93%). However, another meta‐analysis conducted focusing on colorectal lesions ≥ 20 mm suggested that prophylactic clipping could reduce delayed bleeding following EMR, 37 which was consistent with our results. Therefore, we speculate that prophylactic endoscopic closure may be an effective solution to prevent delayed bleeding after ESD or EMR for large colorectal lesions.…”
Section: Discussionsupporting
confidence: 91%
“…found that prophylactic clipping did not reduce the occurrence of delayed bleeding after colorectal endoscopic resection regardless of the lesion size, which the vast majority of the cases enrolled in the analysis are lesions < 20 mm (2847 out of 3059; 93%). However, another meta‐analysis conducted focusing on colorectal lesions ≥ 20 mm suggested that prophylactic clipping could reduce delayed bleeding following EMR, 37 which was consistent with our results. Therefore, we speculate that prophylactic endoscopic closure may be an effective solution to prevent delayed bleeding after ESD or EMR for large colorectal lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Two previous meta-analyses [23,24] showed conflicting results while evaluating the role of HC placement in prevention of DPPB. Forbes et al [23] also included only RCTs but showed no benefit of HCs in prevention of DPPB; pooled RR (95 % CI) 0.86 (0.55, 1.36).…”
Section: Discussionmentioning
confidence: 99%
“…49 In contrast, in a separate randomized trial in 1,098 patients undergoing polypectomy of nonpedunculated polyps ≥10 mm, there was no benefit with closure of mucosal defects using prophylactic endoscopic clipping in reducing the rate of delayed PPB, and this finding was consistent with that obtained for large polyps (≥20 mm). 50 Several systematic reviews and meta-analyses [51][52][53][54][55][56] have consistently shown a similar lack of benefit of prophylactic endoscopic clipping of mucosal defects of nonpedunculated polyps up to 19 mm, with inconclusive benefits for nonpedunculated polyps ≥20 mm. This heterogeneity in polyps ≥20 mm could be due to variations in the polyp location that have not been accounted for in most studies, as was reported in the previously mentioned randomized trial 49 in which a benefit was noted only in the proximal colon.…”
Section: Prevention Of Post-polypectomy Bleedingmentioning
confidence: 99%